Training and Utilization of E-Commerce as a Marketing Media for Micro, Small and Medium Enterprises Products - Eka Resty Novieta Sari; Kelik Sussolaikah; Maylinia Rizky Putri Marwana (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The Micro, Small and Medium Enterprises (MSME) sector during the COVID-19 pandemic has various problems. For example, the decline in sales, capital, hampered distribution, the difficulty of raw materials. The Micro, Small and Medium Enterprises (MSME) actors have also changed their marketing orientation due to the pandemic, many of The Micro, Small and Medium Enterprises (MSME) actors have turned to electronic commerce (e-commerce) to increase sales but this is not supported by the ability of The Micro, Small and Medium Enterprises (MSME) actors who tend to be low in using technology. This service aims to provide understanding and skills for The Micro, Small and Medium Enterprises (MSME) in Sumbersari Village, Saradan District, Kab. Madiun regarding the use of social media as an effective and efficient means of selling/promoting products as well as providing assistance in utilizing various internet-based market places as a means of selling products. This activity uses a contextual approach method, namely providing theoretical material first and followed by a workshop directly uploading the products produced by The Micro, Small and Medium Enterprises (MSME) actors in Sumbersari Village. The result of this activity is the understanding of partners about marketing through social media; able to create a shop on the marketplace and promote it through social media independently